1978
DOI: 10.1111/j.1476-5381.1978.tb08464.x
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Exposure of Rats to the Convulsant Agent Flurothyl Enhances 5‐hydroxytryptamine‐ and Dopamine‐mediated Behavioural Responses

Abstract: 1 Rats were convulsed once daily for 7 days by exposure to the inhalant convulsant agent, flurothyl (Indoklon, bis (2,2,2-trifluouroethyl)ether). Twenty four hours after the final convulsion the rats were injected with tranylcypromine (20 mg/kg) followed 30 min later by L-DOPA (50 mg/kg), a procedure which increases brain dopamine concentrations. The flurothyl-treated rats showed a greater locomotor activity response than rats that had not been convulsed. 2 This enhanced response appears to be due to increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

1978
1978
1991
1991

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(4 citation statements)
references
References 19 publications
2
2
0
Order By: Relevance
“…These data, taken with previous work with the inhalant convulsant flurothyl (Green, 1978) suggest that altered monoamine-mediated behavioural re-sponses may be a consequence of tonic-clonic seizures produced by various different convulsant agents.…”
Section: Number Ofsupporting
confidence: 68%
“…These data, taken with previous work with the inhalant convulsant flurothyl (Green, 1978) suggest that altered monoamine-mediated behavioural re-sponses may be a consequence of tonic-clonic seizures produced by various different convulsant agents.…”
Section: Number Ofsupporting
confidence: 68%
“…These experimentally induced changes resemble the therapeutic effect in that they occur only following a succession of spaced shocks, and also in that they do not occur with peripheral electrical stimulation or with a series of shocks at hourly intervals (Costain et al 1978). Similar changes are seen following convulsions induced by flurothyl (Green, 1978).…”
Section: Animal Experimentssupporting
confidence: 67%
“…Both dopamine and noradrenaline mediated behavioural responses are also enhanced by ECS pretreatment and experiments with agonists indicated that these enhanced responses are due to increased catecholamine post-synaptic responses (GREEN rt a/., 1977: MODIGH, 1975. Such changes are not produced by sub-convulsive shocks (GREEN rt a/., 1977) but can be elicited by flurothyl, an inhalant convulsant (GREEN, 1978) demonstrating the importance of the convulsion.…”
mentioning
confidence: 99%